Validation of the nurse leadership and organizational culture (N-LOC) questionnaire - Juliana Nga Man Lui; Janice Mary Johnston (BMC, 2019)
Abstract Background Leadership style and organizational culture have often been studied independently in nursing research despite abundant evidence that the two factors both influence employee outcomes. Moreover, diverse theoretical typology and measuring instruments challenges generalizability of findings. Employees from different cultural, geographical, occupational settings were also reported to have varying interpretation on organizational culture and leadership style underlying constructs. This study aims to validate the Nursing Leadership and Organizational Culture (N-LOC) questionnaire, based on the two commonly used theoretical frameworks: Multifactor Leadership Theory and Competing Values Framework, on its applicability in an Asian hospital setting. Methods All full-time nurses from two distinctive Asian hospitals (H1: n = 295 and H2: n = 1146) were invited to participate in this questionnaire study. Exploratory factor analysis (EFA) was carried out when confirmatory factor analysis (CFA) fit indices were not satisfactory after model refinement to explore the actual underlying construct in sampled population. Part-time and outsourced nurses were excluded. 93 nurses from H1 were randomly selected for test-retest reliability 4 weeks post initial survey. Scale internal consistency, convergent and discriminant validity were also assessed. Results CFA results indicated that the proposed CVF organizational culture 4-factor structure was applicable to our sample but not the MLQ leadership 3-factor/9-factor structure. EFA revealed a 2-factor leadership style construct for our sample, named Confucius transformational and Laissez-Faire passive leadership. Transformational leadership traits already embedded in Confucius cultural values (self-sacrifice, stresses collective mission, instills pride) did not apply, the new Confucius transformational construct which resembles LMX theory paternalistic leadership style is deemed more suitable in an Asian context. A final 14-item 2-factor leadership and 13-item 4-factor organizational culture construct was yielded with satisfactory fit indices (CFI, TLI > 0.95, RMSEA < 0.08), internal consistency (Cronbach's alpha > 0.7), test-retest reliability (ICC > 0.4) and convergent and discriminant validity. Conclusion A reliable N-LOC organizational culture and leadership questionnaire (N-LOC) has been validated in an Asian nurse context. Study results demonstrated the importance of scale validation in cross-cultural adaptation, as underlying scale constructs may change with specific cultural and contextual factors. Future studies are encouraged to test the adaptation of this scale in other cultural and occupational settings.